A study of dry frictional contacts - Munisamy, R; Munisamy, Richard (1994)
﻿ This study addresses a range of phenomena associated with dry frictional contacts. Particular emphasis is devoted to elastic dissimilarity. Problems are formulated such that coupling between normal and tangential tractions is permitted and the results, which must often be found by numerical means, are compared with classical solutions. The manipulation of objects in contact with frictional surfaces is investigated. The main focus is on objects resting upon a plane at three discrete points of support. When displaced by an arbitrary force such objects have a tendency to rotate about these points of support. The motion of both planar and three dimensional objects is predicted and the effect of friction at the pushing contact is considered. Rolling contact between two elastically dissimilar cylinders is addressed. By allowing full coupling between normal and tangential tractions it is found that an offset in the contact patch may result. This often leads to a significant resistive moment which balances the nett power supplied and the frictional losses. Three dimensional contacts form a major part of the study and a numerical method is developed to facilitate their solution. The evolution of an incomplete contact is evaluated to demonstrate how contact boundaries may be determined. The method is then applied to sliding contact between elastically dissimilar spheres. The traction distributions which result from a fully coupled formulation are compared with those predicted by a Hertzian solution. The parameters which cause the greatest differences are found. A Mindlin-type contact is re-evaluated and traction distributions are calculated which are compatible with local slip directions for both elastically similar and dissimilar bodies. A comprehensive set of results is presented revealing how material parameters influence the solution. Interactions between cracks and contacts are analyzed. It is shown that although the change in compliance of a flawed body may modify the traction distribution compared with a flawless one, the stress intensity factors at the crack tip are rarely affected. Finally, a method of determining the fracture toughness of brittle materials is explored based on the observation of surface cracks in the wake of a sliding indenter. Material characteristics are related to crack initiation, spacing and depth.